2021
DOI: 10.17645/si.v9i4.4649
|View full text |Cite
|
Sign up to set email alerts
|

Double Burden of Disability and Poverty: Does Vocational Rehabilitation Ease the School‐to‐Work Transition?

Abstract: Poor young people more often face health difficulties, (learning) disabilities, and are overrepresented in special schools. Consequently, youth from poor households disproportionately frequently participate in disability‐specific programs aiming to improve their educational levels and labor market opportunities. They face a double burden of disability and poverty. In our study, we look at poor and non‐poor youth with disabilities (YPWD) who participate in vocational rehabilitation (VR) and whether VR helps the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This situation suggests that those with the most significant barriers to employment are less likely to receive this important service. A recent report indicated that the existing VR system is unable to address the multifaceted demands of low-income applicants [ 39 ]. Although consistent with research suggesting that clients with low income tend to continue to have disadvantages into the VR system [ 39 ] this finding suggests the need to more closely examine this issue.…”
Section: Discussionmentioning
confidence: 99%
“…This situation suggests that those with the most significant barriers to employment are less likely to receive this important service. A recent report indicated that the existing VR system is unable to address the multifaceted demands of low-income applicants [ 39 ]. Although consistent with research suggesting that clients with low income tend to continue to have disadvantages into the VR system [ 39 ] this finding suggests the need to more closely examine this issue.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, persons with mental disabilities, frequently coming from special schools where the probability for (higher) educational degrees is lower [ 15 ], most often take part in programs in general and, more specifically, in sheltered workshops. However, if people go into sheltered workshops, their path is predefined for sheltered employment [ 21 , 35 ] and there are very low chances of getting into the first labor market from there [ 36 ]. Furthermore, young persons with psychological disabilities are most often allocated into disability-specific prevocational training programs.…”
Section: Discussionmentioning
confidence: 99%